Scientific Reasoning Abilities Profil of Junior High School Students in Jambi - Rivani Dita Yediarani; Maison Maison; Ahmad Syarkowi (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
This study aims to determine the profile of scientific reasoning ability of junior high school students in Jambi. The type of this research is descriptive quantitative, while the research design using survey type cross-sectional design. The population in this study were junior high school students in Jambi City with a total of 25,789 students. The sampling technique used is cluster sampling. The sample used in this study is 1146 students from 15 schools with different accreditation levels. Techniques of data collection of this study are using the problem of reasoning abilities from lawson's classroom test of scientific reasoning (CTSR) in 2000. The results showed that 100% of the sample is concrete. With the ability of Conservation of matter and volume as the most ability owned by students with the percentage of 16.1% and the lowest ability is the ability of Proportional reasoning with a percentage of 3.0%. This shows that students have not been able to use their reasoning for abstract things. In general, no reasoning ability that has a percentage of 50% indicates that students' reasoning ability in junior high school is still very low and fundamental. Keywords: Profile, scientific reasoning, junior high school, Jambi city